A educação nos assentamentos de sem terra no sudoeste da Bahia: o caso do Assentamento de Amaralina em Vitória da Conquista - Martins, Dinorah Nogueira de Souza (2009)
The present work s goal is to analyze the trajectory of a sector of rural social movements, the landless rural workers at Vitória da Conquista city, at Southwest Bahia State, which at the middle of the seventies decided to start searching for their land. Known as the MST people, this social and political individuals fit at the Movement, focusing to occupy the land and make Agrarian Reform. The occupation of Amaralina s farm at Vitória da Conquista city begins the first landless settling at Southwest Bahia. The research was characterized by a qualitative approach and had as main investigation procedures bibliographic lectures, class and recreational observations, interviews of the residents, coordinator, teachers and students, formulation and application of questionnaires which were answered by 12 children, at the II semester of 2007 and first semester of 2008. This work recovers the fight s history of this people, theirs identity, theirs culture and investigates the offered education at theirs schools and if the pedagogical practice in there is in accordance with the Movement s philosophic and political principles; beginning by MST s history at Brazil and its organization at Southwest Bahia, at the 70ties and 80ties, as well it points to the experiences set and economical social political conflicts seen at the occupation, the land distribution, the production organization, at several breaks and visions and, it opens a precious space for writing at ink the history of this individuals whom had written with blood their owns life history